1996
DOI: 10.1097/00003086-199602000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Mismatch of the Gamma Nail to the Chinese Femur

Abstract: The geometric mismatch of the femoral component of the Gamma nail to the Chinese femora resulted in intraoperative complications. To provide scientific data for modification of the implant, 28 pairs of normal Chinese femora were studied with the 3-dimensional reconstruction from the computed tomography scan data. Measurements were taken from the reconstituted drawings, and the anthropometric data were applied in the modification of the implant. This study is the first report on the application of Chinese anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 7 publications
1
40
0
1
Order By: Relevance
“…In our series, 11 cases of mismatch between the proximal end of the nail and proximal femur were encountered in the short elderly patients. As the height in a Chinese population on average is less than that of Europeans and Americans, the proximal femoral length and femoral neck diameter are relatively shorter [11]. When the PFNA was used in short elderly Chinese patients, the length of the proximal end of the nail proved to be too long, resulting in inappropriate placement of the spiral blade or redundancy of the proximal end of the nail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, 11 cases of mismatch between the proximal end of the nail and proximal femur were encountered in the short elderly patients. As the height in a Chinese population on average is less than that of Europeans and Americans, the proximal femoral length and femoral neck diameter are relatively shorter [11]. When the PFNA was used in short elderly Chinese patients, the length of the proximal end of the nail proved to be too long, resulting in inappropriate placement of the spiral blade or redundancy of the proximal end of the nail.…”
Section: Discussionmentioning
confidence: 99%
“…Leung et al [11] reported the geometric mismatch between the gamma nail and the Chinese femur. A relatively shorter femur and excessive anterior bowing in the older Chinese population lead to the tip of the standard nail or even the shortest nail usually passing beyond the most convex part of the anterior bow.…”
Section: Discussionmentioning
confidence: 99%
“…But they are associated with intra-operative technical and mechanical complications [9,10]. Moreover, geometrical mismatch between proximal femoral nail and the femora of Asians make surgery more difficult and complicated [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Implants that are designed by taking in to account anthropometric and bio mechanic data will help in designing patient specific implants thereby minimizing the complications [21]. Numerous studies have also shown that there is increase in the rate of intraoperative complication in the event of using mismatched implants especially over size implants [19].…”
Section: Resultsmentioning
confidence: 99%